Ceramic slurry suitable for bi-material photocuring 3D printer and preparation method of ceramic slurry
By preparing and printing silicon nitride/boron nitride ceramic slurry in a dual-material photocuring 3D printer, the problem of difficulty in preparing complex structure layered ceramics is solved, and efficient molding and preparation of high-performance ceramic materials are achieved.
Patent Information
- Application Number
- CN202411851233.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to effectively prepare silicon nitride/boron nitride layered ceramics with complex structures, especially in the preparation of variable curvature gyro layered structures.
A dual-material photocuring 3D printer is used to reasonably prepare slurries of silicon nitride and boron nitride, and use raw materials such as photosensitive resin, sintering aid, dispersant and photoinitiator, and ball milling combined with ball milling beads in the ball mill to prepare silicon nitride/boron nitride ceramic slurries suitable for 3D printing.
It realizes efficient molding of large-size complex structures, ensures high interlayer bonding strength, and the printed ceramic materials have high bending strength and fracture toughness, which can meet the needs of complex structures.
Smart Images

Figure CN119684010A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of additive manufacturing materials, and relates to a method for preparing a ceramic slurry suitable for a dual-material light-curing 3D printer and a silicon nitride / boron nitride layered ceramic. Background Art
[0002] In the 1990s, scientists developed high-performance layered silicon nitride / boron nitride composite ceramics based on the structure of the nacre layer of shells. This ceramic has high strength, high toughness, high temperature resistance, and excellent dielectric properties, which meet the requirements of aircraft materials. At the same time, it is very low in cost, making it the preferred material solution for future aircraft.
[0003] At present, the most commonly used methods for preparing ceramic matrix sheets generally include tape casting, extrusion molding, dry pressing molding, centrifugal grouting, etc. For layered composite ceramics with weak interface bonding, the base layer is separated by an intermediate layer. In order to optimize the mechanical properties of composite ceramics, the thickness of the intermediate layer is generally much smaller than the thickness of the base layer. Therefore, in existing research, the base layer molding method is generally not used, and the coating method is usually used. At present, the most widely used coating processes are dip coating and spraying. They all disperse the coating in water and organic solvents to make a uniform and stable solution, suspension or sol, and then immerse the body in the solution or spray the solution evenly on the body, and then dry or gel treat to obtain a uniform coating on the surface of the ceramic sheet.
[0004] These processes are mostly used to prepare flat plates or simple annular ceramic materials, and are difficult to prepare for complex structural components. The development of additive manufacturing has provided a solution to this problem. Additive manufacturing, commonly known as 3D printing, is a preparation technology that constructs three-dimensional components by spreading two-dimensional materials. Ceramic products prepared by this technology can show better results in terms of precision, structural complexity, and comprehensive performance. Using silicon nitride and boron nitride materials for the molding and curing of the printed layers is expected to achieve the integrated molding of low-cost, high-toughness silicon nitride / boron nitride layered composite ceramic complex structures. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the existing technology and provide a method for preparing a ceramic slurry suitable for a dual-material light-curing 3D printer and a silicon nitride / boron nitride layered ceramic to solve the problem of difficulty in preparing a variable curvature rotation body layered structure in the prior art.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] On the one hand, the present invention provides a ceramic slurry suitable for a dual-material light-curing 3D printer, wherein the ceramic slurry is a silicon nitride slurry and a boron nitride slurry; the silicon nitride slurry is prepared from the following raw materials in volume fractions: 30-50% silicon nitride powder, 35-60% photosensitive resin, 5-15% sintering aid, 2.5-5% dispersant, and 0.5-1.5% photoinitiator; the boron nitride slurry is prepared from the following raw materials in volume fractions: 10-30% boron nitride powder, 3-10% alumina powder, 60-80% photosensitive resin, 5-15% sintering aid, 0.5-3% dispersant, and 1-2% photoinitiator.
[0008] Based on the dual-material 3D printing equipment, the ultimate goal is to print silicon nitride / boron nitride layered ceramic composite components and sinter them to meet the requirements, and printing large-sized components is the key to the key. Because it is dual-material printing, it is different from single-material printing. There are differences in the photosensitive properties of silicon nitride slurry and boron nitride slurry. The printing conditions required for printing different materials are different. Therefore, while adjusting the slurry properties during the printing process, the printing parameters also need to be adjusted separately to achieve the bonding of the green body layer and its interlayers. Therefore, it is necessary to conduct in-depth research on the slurry formula of large-sized layered ceramic composite components to achieve a technological breakthrough.
[0009] As a further solution of the present invention, the D50 of the silicon nitride powder is 1 μm to 3 μm, the D50 of the boron nitride powder is 1 μm to 5 μm, and the D50 of the aluminum oxide powder is 0.5 μm to 1 μm.
[0010] As a further solution of the present invention, the particle size D50 of the silicon nitride powder is one of 1 μm, 2 μm and 3 μm.
[0011] As a further solution of the present invention, the particle size D50 of the boron nitride powder is one of 1 μm, 3 μm and 5 μm.
[0012] As a further embodiment of the present invention, the particle size D50 of the alumina powder is one of 0.5 μm, 0.7 μm and 1 μm.
[0013] As a further solution of the present invention, the dispersant is one of KOS110 and KOS163 or a mixture of the two.
[0014] As a further embodiment of the present invention, the photosensitive resin includes photosensitive resin A and photosensitive resin B; photosensitive resin A is selected from at least one of hydroxyethyl methacrylate, 1,6-hexanediol diacrylate, and propoxylated neopentyl glycol diacrylate; photosensitive resin B is selected from at least one of trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, and epoxy methacrylate; the volume ratio of the photosensitive resin A to the photosensitive resin B is 1:1-1:4.
[0015] As a further embodiment of the present invention, the photoinitiator is selected from 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0016] As a further solution of the present invention, the solid content of the silicon nitride slurry is 30-50%; the solid content of the boron nitride slurry is 10-30%.
[0017] As a further solution of the present invention, the sintering aid in the silicon nitride slurry is at least one of aluminum oxide, silicon dioxide, boron nitride, and yttrium oxide powder; and the sintering aid in the boron nitride slurry is boron oxide.
[0018] In another aspect, the present invention provides a method for preparing silicon nitride / boron nitride ceramic slurry for 3D printing, comprising at least:
[0019] Silicon nitride powder is mixed evenly with photosensitive resin, sintering aid, dispersant and photoinitiator, and boron nitride powder and alumina powder are mixed evenly with photosensitive resin, sintering aid, dispersant and photoinitiator to obtain the silicon nitride slurry and boron nitride slurry for 3D printing.
[0020] As a further solution of the present invention: the method specifically comprises:
[0021] S1, adding the dispersant to the photosensitive resin, mixing evenly, to obtain material A;
[0022] S2, adding the mixed powder of silicon nitride or boron nitride and aluminum oxide to the material A to obtain material B;
[0023] S3, adding the sintering aid to the material B, and ball milling to obtain material C;
[0024] S4. Add the initiator to the material C and stir until the initiator is completely dissolved to obtain the silicon nitride slurry or boron nitride slurry for 3D printing.
[0025] In the present invention, in step S3, after material B is poured into a ball mill, 5 mm, 10 mm, and 15 mm ball milling beads are added for ball milling.
[0026] As a further solution of the present invention: in step S3, the ball milling time is 2-24 hours; the ball milling rotation direction is first clockwise and then counterclockwise.
[0027] Optionally, the ball milling time is independently selected from 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h.
[0028] As a further solution of the present invention: before step S1, the method further comprises: pre-treating the silicon nitride powder or boron nitride powder, specifically, wet ball milling for 4 hours, drying, and passing through a 100-mesh sieve.
[0029] In another aspect, the present invention provides a dual-material light-curing 3D printing method, comprising the following steps:
[0030] Put the silicon nitride slurry and the boron nitride slurry into a 3D printer, adjust the printing parameters, and print according to a preset structural model;
[0031] The printing parameters include: printer LED light source wavelength 405nm; printing layer thickness 10-100 microns; light intensity 6000-19000μw / cm 2 ; Number of bottom exposure layers: 0-5; bottom exposure time: 50-150s; exposure time for each layer: 2-50s; thickness of silicon nitride layer: 100-500 microns, thickness of boron nitride layer: 10-50 microns.
[0032] On the other hand, the present invention provides a silicon nitride / boron nitride layered ceramic, characterized in that the layered ceramic is prepared using the above-mentioned ceramic slurry suitable for a dual-material photocuring 3D printer, and the layered ceramic includes a silicon nitride layer and a boron nitride layer.
[0033] As a further solution of the present invention: the thickness of the silicon nitride layer is 100-500 microns, and the thickness of the boron nitride layer is 10-50 microns.
[0034] The beneficial effects of the present invention are:
[0035] The present invention prepares silicon nitride / boron nitride slurry with good dispersibility and curing effect by selecting suitable photosensitive resin, dispersant, and initiator types, controlling the addition ratio of each raw material and the particle size of silicon nitride / boron nitride powder, and does not cause the problem of insufficient interlayer bonding strength due to different slurries and low curing depth during 3D printing. The silicon nitride / boron nitride slurry of the present invention can be quickly cured during the printing process of the additive manufacturing digital light processing photocuring 3D printer, and the curing thickness is greater than 30 microns. The interface bonding strength of the printed sample is high, the size accuracy of the printed sample is better, and complex layered structures can be formed and high-toughness ceramic materials can be obtained by designing the layer thickness ratio. The ceramic sample after final sintering has high bending strength and fracture toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The silicon nitride slurry and boron nitride slurry for dual-material 3D printing prepared in Example 1 of the present invention;
[0037] Figure 2 This is the silicon nitride / boron nitride ceramic sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below through specific embodiments.
[0039] Example 1
[0040] Step S1, weighing 42 parts of a mixed photosensitive resin obtained by uniformly mixing 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 1:1;
[0041] Step S2, adding 2.5 parts of dispersant KOS163, mixing and shaking for 5 hours;
[0042] Step S3, pouring the mixed solution into a ball mill, adding 2-3 mm ceramic balls for stirring, adding 50 parts of silicon nitride powder and then ball milling for 12 hours, wherein the D50 of the silicon nitride particles is 1.5 μm;
[0043] Step S4, adding 3.5 parts of sintering aids, wherein the sintering aids are aluminum oxide, silicon dioxide, boron nitride, and yttrium oxide, and the mass ratio is 1:1.5:1.5:1;
[0044] Step S5, adding 2 parts of an initiator, wherein the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours until the initiator is completely dissolved, to obtain a silicon nitride slurry with a solid content of 50%;
[0045] Step S6, weighing 66.5 parts of a mixed photosensitive resin obtained by uniformly mixing 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 1:4;
[0046] Step S7, adding 1.5 parts of dispersant KOS163, mixing and shaking for 5 hours;
[0047] Step S8, pour the mixed solution into a ball mill, add 2-3 mm ceramic balls for stirring, add 30 parts of boron nitride powder and alumina powder and then perform ball milling (the volume ratio of boron nitride to alumina is 3:1), the ball milling time is 12 hours, wherein the D50 of the boron nitride particles is 1 μm, and the D50 of the alumina particles is 0.5 μm;
[0048] Step S9, adding 1.5 parts of a sintering aid, wherein the sintering aid is boron oxide;
[0049] Step S10, adding 1.5 parts of an initiator, wherein the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours until the initiator is completely dissolved, to obtain a boron nitride slurry with a solid content of 30%;
[0050] Step S11, putting the prepared silicon nitride slurry and boron nitride slurry into a 3D printer with a wavelength of 405nm, with a light intensity of 6000-19000μw / cm2, 2 bottom exposure layers, and a bottom exposure time of 150s; then adjusting the layer thickness to 50μm and the exposure time to 10s, alternately completing the 3D printing of the layered structure of silicon nitride / boron nitride ceramics, with a silicon nitride layer thickness of 300μm and a boron nitride layer thickness of 30μm.
[0051] The printed ceramic sample has a bending strength of 213.21MPa and a fracture toughness of 10.14MPa·m1 / 2 after debinding and sintering.
[0052] The silicon nitride slurry and boron nitride slurry for dual-material 3D printing prepared in this embodiment are as follows: Figure 1 As shown, the silicon nitride / boron nitride ceramic sample prepared in this embodiment is as follows Figure 2 shown.
[0053] Example 2
[0054] The difference from Example 1 is that in step S1, 47 parts of a mixed photosensitive resin prepared by uniformly mixing 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 1:2 are weighed;
[0055] Step S3, pouring the mixed solution into a ball mill, adding 2-3 mm ceramic balls for stirring, adding 45 parts of silicon nitride powder and then ball milling for 12 hours, wherein the D50 of the silicon nitride particles is 1.5 μm;
[0056] Step S5, adding 2 parts of an initiator, the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours until the initiator is completely dissolved, to obtain a silicon nitride slurry with a solid content of 45%;
[0057] The printed ceramic sample has a bending strength of 195.18MPa and a fracture toughness of 8.57MPa·m1 / 2 after debinding and sintering.
[0058] Example 3
[0059] The difference from Example 1 is that in step S1, 52 parts of a mixed photosensitive resin in which 1,6-hexanediol diacrylate and trimethylolpropane triacrylate are uniformly mixed in a volume ratio of 1:3 are weighed;
[0060] Step S3, pouring the mixed solution into a ball mill, adding 2-3 mm ceramic balls for stirring, adding 40 parts of silicon nitride powder and then ball milling for 12 hours, wherein the D50 of the silicon nitride particles is 1.5 μm;
[0061] Step S5, adding 2 parts of an initiator, the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours until the initiator is completely dissolved, to obtain a silicon nitride slurry with a solid content of 40%;
[0062] The printed ceramic sample has a bending strength of 187.67MPa and a fracture toughness of 7.54MPa·m1 / 2 after debinding and sintering.
[0063] Example 4
[0064] The only difference from Example 1 is that in step S6, 71.5 parts of a mixed photosensitive resin in which 1,6-hexanediol diacrylate and trimethylolpropane triacrylate are uniformly mixed in a volume ratio of 1:3 are weighed;
[0065] Step S8, pour the mixed solution into a ball mill, add 2-3 mm ceramic balls for stirring, add 25 parts of boron nitride powder and alumina powder and then perform ball milling (the volume ratio of boron nitride to alumina is 3:1), the ball milling time is 12 hours, wherein the D50 of the boron nitride particles is 1 μm, and the D50 of the alumina particles is 0.5 μm;
[0066] Step S10, adding 1.5 parts of an initiator, wherein the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours until the initiator is completely dissolved, to obtain a boron nitride slurry with a solid content of 25%;
[0067] The printed ceramic sample has a bending strength of 200.44MPa and a fracture toughness of 8.69MPa·m1 / 2 after debinding and sintering.
[0068] Example 5
[0069] The only difference from Example 1 is that in step S6, 76.5 parts of a mixed photosensitive resin prepared by uniformly mixing 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 1:3 are weighed;
[0070] Step S8, pour the mixed solution into a ball mill, add 2-3 mm ceramic balls for stirring, add 20 parts of boron nitride powder and alumina powder and then perform ball milling (the volume ratio of boron nitride to alumina is 3:1), the ball milling time is 12 hours, wherein the D50 of the boron nitride particles is 1 μm, and the D50 of the alumina particles is 0.5 μm;
[0071] Step S10, adding 1.5 parts of an initiator, wherein the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours until the initiator is completely dissolved, to obtain a boron nitride slurry with a solid content of 20%;
[0072] The printed ceramic sample has a bending strength of 184.35MPa and a fracture toughness of 7.43MPa·m1 / 2 after debinding and sintering.
[0073] Example 6
[0074] The only difference from Example 1 is that in step S6, 81.5 parts of a mixed photosensitive resin prepared by uniformly mixing 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 1:2 is weighed;
[0075] Step S8, pour the mixed solution into a ball mill, add 2-3 mm ceramic balls for stirring, add 15 parts of boron nitride powder and alumina powder and then perform ball milling (the volume ratio of boron nitride to alumina is 3:1), the ball milling time is 12 hours, wherein the D50 of the boron nitride particles is 1 μm, and the D50 of the alumina particles is 0.5 μm;
[0076] Step S10, adding 1.5 parts of an initiator, wherein the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours until the initiator is completely dissolved, to obtain a boron nitride slurry with a solid content of 15%;
[0077] The printed ceramic sample has a bending strength of 174.23MPa and a fracture toughness of 6.44MPa·m1 / 2 after debinding and sintering.
[0078] Example 7
[0079] The only difference from Example 1 is that in step S6, 86.5 parts of a mixed photosensitive resin prepared by uniformly mixing 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 1:1 are weighed;
[0080] Step S8, pour the mixed solution into a ball mill, add 2-3 mm ceramic balls for stirring, add 10 parts of boron nitride powder and alumina powder and then perform ball milling (the volume ratio of boron nitride to alumina is 3:1), the ball milling time is 12 hours, wherein the D50 of the boron nitride particles is 1 μm, and the D50 of the alumina particles is 0.5 μm;
[0081] Step S10, adding 1.5 parts of an initiator, wherein the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours until the initiator is completely dissolved, to obtain a boron nitride slurry with a solid content of 10%;
[0082] The printed ceramic sample has a bending strength of 157.25MPa and a fracture toughness of 3.45MPa·m1 / 2 after debinding and sintering.
[0083] Example 8
[0084] The only difference from Example 1 is that in step S6, 67.5 parts of a mixed photosensitive resin of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate uniformly mixed in a volume ratio of 1:4 are weighed;
[0085] Step S9, adding 0.5 parts of a sintering aid, wherein the sintering aid is boron oxide.
[0086] The printed ceramic sample has a bending strength of 184.23MPa and a fracture toughness of 7.86MPa·m1 / 2 after debinding and sintering.
[0087] Example 9
[0088] The difference from Example 1 is that in step S8, the mixed solution is poured into a ball mill, 2-3 mm ceramic balls are added for stirring, 30 parts of boron nitride powder and alumina powder are added and then ball milled (the volume ratio of boron nitride to alumina is 1:1), and the ball milling time is 12 hours, wherein the D50 of the boron nitride particles is 1 μm, and the D50 of the alumina particles is 0.5 μm;
[0089] The printed ceramic sample has a bending strength of 224.12MPa and a fracture toughness of 7.45MPa·m1 / 2 after debinding and sintering.
[0090] Example 10
[0091] The only difference from Example 9 is that in step S8, the mixed solution is poured into a ball mill, 2-3 mm ceramic balls are added for stirring, 30 parts of boron nitride powder are added and ball milled for 12 hours, wherein the D50 of the boron nitride particles is 1 μm, and the D50 of the alumina particles is 0.5 μm;
[0092] The printed ceramic sample has a bending strength of 130.75MPa and a fracture toughness of 9.03MPa·m1 / 2 after debinding and sintering.
[0093] Embodiment 11
[0094] The only difference from Example 1 is that in step S11, the prepared silicon nitride slurry and boron nitride / aluminum oxide slurry are placed in a 3D printer with a wavelength of 405 nm, the light intensity is 6000-19000 μw / cm2, the number of bottom exposure layers is 2, and the bottom exposure time is 150 s; then the layer thickness is adjusted to 50 μm, the exposure time is 10 s, and the layered structure of 3D printed silicon nitride / boron nitride ceramics is alternately completed, with a silicon nitride layer thickness of 200 μm and a boron nitride layer thickness of 50 μm.
[0095] The printed ceramic sample has a bending strength of 179.34MPa and a fracture toughness of 7.61MPa·m1 / 2 after debinding and sintering.
[0096] Example 12
[0097] The only difference from Example 1 is that in step S11, the prepared silicon nitride slurry and boron nitride / aluminum oxide slurry are placed in a 3D printer with a wavelength of 405 nm, the light intensity is 6000-19000 μw / cm2, the number of bottom exposure layers is 2, and the bottom exposure time is 150 s; then the layer thickness is adjusted to 50 μm, the exposure time is 10 s, and the layered structure of 3D printed silicon nitride / boron nitride ceramics is alternately completed, with a silicon nitride layer thickness of 100 μm and a boron nitride layer thickness of 100 μm.
[0098] The printed ceramic sample has a bending strength of 147.63MPa and a fracture toughness of 5.48MPa·m1 / 2 after debinding and sintering.
[0099] Comparative Example 1
[0100] The difference from Example 1 is that in step S1, 37 parts of a mixed photosensitive resin prepared by uniformly mixing 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 1:1 are weighed;
[0101] Step S3, pouring the mixed solution into a ball mill, adding 2-3 mm ceramic balls for stirring, adding 55 parts of silicon nitride powder and then ball milling for 12 hours, wherein the D50 of the silicon nitride particles is 1.5 μm;
[0102] Step S5, adding 2 parts of an initiator, the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours. The viscosity is too high to obtain silicon nitride slurry.
[0103] Comparative Example 2
[0104] The only difference from Example 1 is that in step S6, 61.5 parts of a mixed photosensitive resin prepared by uniformly mixing 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a volume ratio of 1:4 is weighed;
[0105] Step S8, pour the mixed solution into a ball mill, add 2-3 mm ceramic balls for stirring, add 35 parts of boron nitride powder and alumina powder and then perform ball milling (the volume ratio of boron nitride to alumina is 3:1), the ball milling time is 12 hours, wherein the D50 of the boron nitride particles is 1 μm, and the D50 of the alumina particles is 0.5 μm;
[0106] Step S10, adding 1.5 parts of an initiator, the initiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and continuing to stir in the ball mill for 6 hours. The viscosity is too high to obtain a boron nitride slurry.
[0107] Comparative Example 3
[0108] The only difference from Example 1 is that in step S11, the prepared silicon nitride slurry and boron nitride / aluminum oxide slurry are placed in a 3D printer with a wavelength of 405 nm, the light intensity is 6000-19000 μw / cm2, the number of bottom exposure layers is 2, and the bottom exposure time is 150 s; then the layer thickness is adjusted to 50 μm, the exposure time is 10 s, and the layered structure of 3D printed silicon nitride / boron nitride ceramics is alternately completed, with a silicon nitride layer thickness of 300 μm and a boron nitride layer thickness of 10 μm.
[0109] The printed ceramic sample undergoes interlayer delamination after debinding and sintering.
[0110] Comparative Example 4
[0111] The only difference from Example 1 is that in step S11, the prepared silicon nitride slurry and boron nitride / aluminum oxide slurry are placed in a 3D printer with a wavelength of 405 nm, the light intensity is 6000-19000 μw / cm2, the number of bottom exposure layers is 0 layer; the bottom exposure time is 0 s; then the layer thickness is adjusted to 50 μm, the exposure time is 10 s, and the layered structure of 3D printed silicon nitride / boron nitride ceramics is alternately completed, with a silicon nitride layer thickness of 300 μm and a boron nitride layer thickness of 30 μm.
[0112] The ceramic sample obtained in this comparative example cannot be formed on the forming table.
[0113] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various replacements, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.
Claims
1. A ceramic slurry suitable for a dual-material light-curing 3D printer, characterized in that: The ceramic slurry is silicon nitride slurry and boron nitride slurry; the silicon nitride slurry is prepared from the following raw materials in volume fractions: 30-50% silicon nitride powder, 35-60% photosensitive resin, 5-15% sintering aid, 2.5-5% dispersant, and 0.5-1.5% photoinitiator; the boron nitride slurry is prepared from the following raw materials in volume fractions: 10-30% boron nitride powder, 3-10% alumina powder, 60-80% photosensitive resin, 5-15% sintering aid, 0.5-3% dispersant, and 1-2% photoinitiator.
2. The ceramic slurry suitable for a dual-material light-curing 3D printer according to claim 1, characterized in that: The D50 of the silicon nitride powder is 1 μm to 3 μm, the D50 of the boron nitride powder is 1 μm to 5 μm, and the D50 of the aluminum oxide powder is 0.5 μm to 1 μm.
3. The ceramic slurry suitable for a dual-material light-curing 3D printer according to claim 1, characterized in that: The dispersant is at least one of KOS110 and KOS163; the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the sintering aid in the silicon nitride slurry is at least one of aluminum oxide, silicon dioxide, boron nitride, and yttrium oxide powder, and the sintering aid in the boron nitride slurry is boron oxide.
4. The ceramic slurry suitable for a dual-material light-curing 3D printer according to claim 1, characterized in that: The photosensitive resin includes photosensitive resin A and photosensitive resin B; photosensitive resin A is selected from at least one of hydroxyethyl methacrylate, 1,6-hexanediol diacrylate, and propoxylated neopentyl glycol diacrylate; photosensitive resin B is selected from at least one of trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, and epoxy methacrylate; the volume ratio of the photosensitive resin A to the photosensitive resin B is 1:1-1:
4.
5. The ceramic slurry suitable for a dual-material light-curing 3D printer according to claim 1, characterized in that: The solid content of the silicon nitride slurry is 30-50%, and the solid content of the boron nitride slurry is 10-30%.
6. A method for preparing a ceramic slurry suitable for a dual-material light-curing 3D printer, characterized in that: The following steps are involved: Add the dispersant to the photosensitive resin and mix well to obtain material A; Adding silicon nitride powder or a mixed powder of boron nitride powder and aluminum oxide powder to material A to obtain material B; Add sintering aid to material B and ball mill to obtain material C; A photoinitiator is added to material C and stirred until the photoinitiator is completely dissolved to prepare silicon nitride slurry or boron nitride slurry for 3D printing.
7. The preparation method according to claim 6, characterized in that: The ball milling time is 2-24 hours, and the ball milling direction is first clockwise and then counterclockwise.
8. A dual-material light-curing 3D printing method, characterized in that: The following steps are involved: Put the ceramic slurry suitable for a dual-material light-curing 3D printer according to any one of claims 1 to 5 into a 3D printer material tank, adjust the printing parameters, and print according to a preset structural model; The printing parameters include: printer LED light source wavelength 405nm; printing layer thickness 10-100 microns; light intensity 6000-19000μw / cm 2 ; Number of bottom exposure layers: 0-5; bottom exposure time: 50-150s; exposure time for each layer: 2-50s; thickness of silicon nitride layer: 100-500 microns, thickness of boron nitride layer: 10-50 microns.
9. A silicon nitride / boron nitride layered ceramic, characterized in that: The layered ceramic is prepared using the ceramic slurry suitable for a dual-material photocurable 3D printer according to any one of claims 1 to 5, and the layered ceramic comprises a silicon nitride layer and a boron nitride layer.
10. The silicon nitride / boron nitride layered ceramic according to claim 9, characterized in that: The thickness of the silicon nitride layer is 100-500 microns, and the thickness of the boron nitride layer is 10-50 microns.
Citation Information
Cited By
Aluminum oxynitride transparent ceramic photosensitive slurry based on DLP-3D printing and preparation method and application thereof
CN122482822A